An update to the fatty acid profiles of bovine retail milk in the United Kingdom: Implications for nutrition in different age and gender groups. (15th March 2019) - Stergiadis, Sokratis; Berlitz, Carolina B.; Hunt, Benjamin; Garg, Sneha; Ian Givens, D.; Kliem, Kirsty E.
Highlights: The fatty acid profile of conventional, organic and free-range retail milk was assessed. Organic milk had overall more omega-3 fatty acids and less palmitic acid. Free-range milk had similar fat profile to conventional milk. Milk fat supplies around one-third the maximum reference saturated fat intake. Consuming different milks changes fatty acid intakes but health effects are unknown. Abstract: This study investigated the effect of UK dairy production system, month, and their interaction, on retail milk fatty acid (FA) profile throughout the year. Milk samples (n = 120) from four conventional (CON), four organic (ORG) and two free-range (FR) brands were collected monthly. ORG milk had more nutritionally-desirable polyunsaturated FA, including rumenic acid and the omega-3 PUFA α-linolenic, eicosapentaenoic and docosapentaenoic acids, and less of the nutritionally-undesirable palmitic acid. Milk FA profile was similar between FR and CON systems, but FR milk had less saturated FA (SFA) and/or palmitic acid, and/or greater α-linolenic and rumenic acids in certain months within the peak-grazing season. According to the measured milk FA profiles and UK milk fat intakes, milk and dairy products contribute around one-third of the maximum recommended SFA intake. A small increased intake of beneficial PUFA may be expected by consuming ORG milk but human health implications from such differences are unknown.